New species of Ceratoderus and Melanospilus from Southeast Asia (Coleoptera: Carabidae: Paussinae) - Bednařík, Michal (Zootaxa, 2023)
Ceratoderus Westwood, 1841 and Melanospilus Westwood, 1847 are highly modified Paussinae ground beetles placed in close relationships with Paussus Linnaeus, 1775 in the latest studies. Four new species are described from Southeast Asia: Ceratoderus anthicoides sp. nov. (Philippines), C. kalamensis sp. nov. (Sulawesi), Melanospilus pilosus sp. nov. (Malay Peninsula), and M. spectabilis sp. nov. (Thailand). The present findings show how diversity is incompletely known, even in areas where many entomologists conducted field research.